If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + -6(8v + -6) = -4 + -3v Reorder the terms: 5 + -6(-6 + 8v) = -4 + -3v 5 + (-6 * -6 + 8v * -6) = -4 + -3v 5 + (36 + -48v) = -4 + -3v Combine like terms: 5 + 36 = 41 41 + -48v = -4 + -3v Solving 41 + -48v = -4 + -3v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '3v' to each side of the equation. 41 + -48v + 3v = -4 + -3v + 3v Combine like terms: -48v + 3v = -45v 41 + -45v = -4 + -3v + 3v Combine like terms: -3v + 3v = 0 41 + -45v = -4 + 0 41 + -45v = -4 Add '-41' to each side of the equation. 41 + -41 + -45v = -4 + -41 Combine like terms: 41 + -41 = 0 0 + -45v = -4 + -41 -45v = -4 + -41 Combine like terms: -4 + -41 = -45 -45v = -45 Divide each side by '-45'. v = 1 Simplifying v = 1
| 3p+3-6p+4=1-3p+6 | | 3x-18/2=6 | | v+1=-1-v | | 100=20+30+40+x | | 3y+5-2y=10 | | -2(-4+n)=46 | | 0.8m+4=16 | | 17=3(x+1)-4y | | -10y^2+3y=-9 | | -8-x=x-4cx | | f/3-10=15 | | http://webwork.math.ttu.edu/webwork2/f15abelhadm1550s012 | | 2x(x-2)-3(x+1)=2(x+1)(x-2) | | 8+2x=-4x+38 | | 2/5*4,500 | | log(3)(5x+13)-log(3)6=2 | | 2y-4/3=5/3 | | f/3=10=15 | | 1/4(6 | | 4-2m=5n | | 3(2y-1)+y=y-3 | | 2(2y-1)+y=y-3 | | -4+z=12 | | Y=2x+(-4) | | a/2=1/6 | | -6b+2b=16 | | 13x+18=4x-27 | | 0.4b+6=10 | | 3(2y-1)+1=y-3 | | -4-3d=11d-8 | | -5n-6(7n+6)=9(-4+9n) | | 2(2y-1)+1=y-3 |